Analysis of the consumption of energy drinks, fruit juices and other beverages among young athletes - Nowak, Dariusz (Journal of Education, Health and Sport, 2019)
Energy drinks are very popular among young people. The aim of the study was to analyze the consumption of energy drinks on a group of young athletes after nutritional education. The study was conducted on a group of 247 young athletes in two randomly chosen sports schools in Bydgoszcz. Studies carried out in two stages (before and after nutritional education) using author's questionnaire and FFQ. EDs were consumed by 66% (I stage) and 69% (II stage) of the young athletes. Most young athletes chose energy drinks based on taste (63.5%) and price (40%). Nutritional education have made that the number of young athletes consuming EDs quite often (i.e. daily, 1-3 times a week) decreased significantly from 28.3% to 19.7%. Nutritional education also influenced the good nutritional choices of young athletes. Of the drinks, the most young athletes consumed daily still mineral water (42%) and fruit juices (13%), with less consumption of cola-type caffeine drinks (7%). The study showed that nutritional education have reduced the frequent consumption of EDs among young athletes.